Analysis of the expression patterns of the cytokine receptor family B (CRFB) and interferon gamma receptor (IFNGR) in Dabry's sturgeon (Acipenser dabryanus). (July 2018) - Luo, Kai; Zhang, Shuhuan; Tang, Dongdong; Xia, Lihai; Gao, Weihua; Tian, Guangming; Qi, Zhitao; Xu, Qiaoqing; Zhang, Wenbing
Abstract: Teleost fish have more complex interferon receptor systems than mammals. In the present study, genes encoding four cytokine receptor family B (CRFBs) and two interferon gamma receptors (IFNGRs) in Dabry's sturgeon ( Acipenser dabryanus ) were identified by RNA-sequencing. Sequence analysis revealed that the Dabry's sturgeon CRFBs and IFNGRs contained several conserved characteristics features, including signal peptides and a transmembrane domain. Phylogenetic analysis suggested that they belong to the CRFB3, CRFB5, and IFNGR protein families, and were named CRFB3a, CRFB3b, CRFB5a, CRFB5b, IFNGR1, and IFNGR2. The expression patterns of the CRFB and IFNGR genes were investigated in Dabry's sturgeon. The expression levels of CRFB5a, CRFB5b, and IFNGR1 showed no significant changes, suggesting that those genes do not mediate embryonic development. By contrast, the high expression levels of CRFB3a, CRFB3b, and IFNGR2 in the fertilized egg, 16-cell phase, and initial blastula stage implied the existence of maternally expression in the oocyte and association with embryonic development. Tissue distribution analysis revealed that the CRFB and IFNGR proteins have potential functions in immune and non-immune tissue compartments. Comprehensive analysis in Dabry's sturgeon revealed that the expression fold changes of CRFB3a, CRFB3b, CRFB5a, and CRFB5b in Dabry's sturgeon stimulated with poly I:C were higher than those in fish administrated with lipopolysaccharide (LPS). Conversely, the fold changes IFNGRs mRNA levels stimulated with LPS were higher than those in fish administrated with poly I: C. CRFB5a and IFNGR2 genes showed the earliest responses to the poly I: C, and the CRFB5a and IFNGR1 genes showed the earliest responses to LPS. These results implied that CRFB5a has important role in the IFN immune response. Our findings indicated that the Dabry's sturgeon CRFB and IFNGR genes have important functions in antiviral and antibacterial immune responses. The differential responses of these genes to poly I: C and LPS implied differences in the defense mechanisms against viruses and bacteria. Highlights: This manuscript describes the identification of four CRFB genes and two IFNGR genes in Dabry's sturgeon. The study was mainly based on expression analysis, investigating the expression level of the six genes in stimulated or non-stimulated conditions. The expression level of CRFBs and IFNGR genes are different after incubation with Poly I:C or LPS stimulation.